Analysis of quantisation noise within signal band for sinusoidal signal. Issue 4 (1st March 2013) - Tian, Pengwu; Kang, Rongzong; Yu, Hongyi; Wu, Ying
Abstract : This study re‐examines the spectrum of quantisation noise and studies the quantisation noise within signal band for sinusoid signals and for uniform quantiser. Both the process of sampling and folding which have not been fully taken into account in previous analysis are considered theoretically. The authors' results show that the quantisation noise within signal band for sinusoid input decreases in broken line as the sampling rate increases, which suggests that a higher signal to in‐band quantisation noise ratio will be obtained if the sinusoid signal is sampled at odd multiple of its fundamental frequency. Moreover, the effects of quantisation step size and the amplitude of sinusoid signal to in‐band quantisation noise are presented by computer simulations.